2003
DOI: 10.1097/01.alc.0000052584.05305.98
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Frontocerebellar Circuitry and Function in Alcoholism

Abstract: This article represents a symposium of the 2002 joint meeting of RSA and ISBRA held in San Francisco. Presentations were Neuropathology of alcohol-related cerebellar damage in humans, by Antony J. Harding; Neuropathological evidence of cerebellar damage in an animal model of alcoholism, by Roberta Pentney and Cynthia Dlugos; Understanding cortical-cerebellar circuits through neuroimaging study of chronic alcoholics, by Peter R. Martin and Mitchell H. Parks; and Functional reorganization of the brain in alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
103
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 57 publications
9
103
0
1
Order By: Relevance
“…The DLPFC, ACC, and insula are fundamentally involved in decision making, problem solving, impulse control, regulation of mood and affect, craving, and evaluation and anticipation of stimulus salience and hedonics (Baler and Volkow, 2006;Paulus, 2007;Redish et al, 2008;Sinha and Li, 2007). The cerebellum is associated with aspects of learning and memory, working memory, executive skills, and reward processing (Anderson et al, 2006;Martin-Solch et al, 2001;Paul et al, 2009;Sullivan, 2003;Sullivan et al, 2003), and the corona radiata provides reciprocal connections linking frontal, parietal, and temporal neocortical regions and subcortical structures (Aralasmak et al, 2006;Makris et al, 1999;Schmahmann et al, 2007). Neurobiological abnormalities in these regions are linked to cognitive, emotional, and behavior disturbances that may confer risk for the relapse/remit cycle commonly observed in all substance-use disorders (Crews and Boettinger, 2009;Kalivas and O'Brien, 2008;Kalivas and Volkow, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DLPFC, ACC, and insula are fundamentally involved in decision making, problem solving, impulse control, regulation of mood and affect, craving, and evaluation and anticipation of stimulus salience and hedonics (Baler and Volkow, 2006;Paulus, 2007;Redish et al, 2008;Sinha and Li, 2007). The cerebellum is associated with aspects of learning and memory, working memory, executive skills, and reward processing (Anderson et al, 2006;Martin-Solch et al, 2001;Paul et al, 2009;Sullivan, 2003;Sullivan et al, 2003), and the corona radiata provides reciprocal connections linking frontal, parietal, and temporal neocortical regions and subcortical structures (Aralasmak et al, 2006;Makris et al, 1999;Schmahmann et al, 2007). Neurobiological abnormalities in these regions are linked to cognitive, emotional, and behavior disturbances that may confer risk for the relapse/remit cycle commonly observed in all substance-use disorders (Crews and Boettinger, 2009;Kalivas and O'Brien, 2008;Kalivas and Volkow, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cerebellum and corona radiata are not considered to be core components of the brain reward system, there is a clear rationale for their inclusion as constituents of the reward system. The cerebellum is involved in aspects of learning and memory, working memory, executive skills, and reward processing (Anderson et al, 2006;Martin-Solch et al, 2001;Olbrich et al, 2006;Paul et al, 2009;Sullivan, 2003;Sullivan et al, 2003). The corona radiata is comprised of projection bundles (e.g., corticothalamic, corticostriatal, corticopontine) and reciprocal fi bers that link frontal, parietal, and temporal neocortical regions and subcortical nuclei involved in executive skills, impulse control, emotional regulation, and reward processing (Aralasmak et al, 2006;Cummings, 1995Cummings, , 1998Makris et al, 1999;Mega and Cummings, 1994;Saint-Cyr, 2003;Schmahmann et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, animal models have recently revealed alcohol-related dendritic regression within Purkinje neurons (Dlugos & Pentney, 2002) that appears to be reversible following ethanol withdrawal (Dlugos & Pentney, 1997). The processes involved in dendritic regression and subsequent reconstruction are highly complex, and their effects on neuronal processing downstream are completely unknown (Sullivan et al, 2003).…”
Section: Eyeblink Classical Associative Learning: Neuronal Circuit Anmentioning
confidence: 99%
“…A loss of synapses, resulting from alcohol abuse, can cause some of the abnormal movements often seen in alcohol abusers, such as unsteady gait, tremors and lack of coordination. In addition, other deficits have been associated with alcohol use and abuse, including impairments in the following cognitive functions: memory, verbal learning, abstract thinking, problemsolving, perceptual analysis and synthesis, speed of information and efficiency, as well as perceptual motor skills [24,[47][48][49][50][51][52][53] . Also, research found that when compared to cocaine, alcohol had more negative effects on attention and executive functioning [22] .…”
Section: Introductionmentioning
confidence: 99%